The Roles of Identity Conflict, Emotion, and Threat in Learning from Refutation Texts on Vaccination and Immigration. Issue 1 (7th February 2022) - Trevors, Gregory J.
ABSTRACT: It is common for individuals to have misconceptions across a range of subject matters. Although interventions to correct misconceptions are largely successful, at times they may fail. The current study explores how corrections may be perceived to conflict with aspects of personal or social identity and engender experience of negative emotions and threat as potential explanations for why and how corrections fail. To test this assumption, purposeful sampling was used to recruit participants online that resided in geographic regions with reported beliefs or behaviors that were consistent with misconceptions about immigration and crime or vaccination safety. Participants reported their prior beliefs and attitudes. Depending on the topic, participants were presented with a refutation text that was designed to correct common misconceptions about vaccination or immigration and were asked to report the degree of identity conflict, emotions, and threat experienced and completed a posttest of knowledge. Results showed that participants reported a significant degree of identity conflict and threat, which together with negative emotions in turn negatively predicted learning from refutation texts. Findings demonstrate potential explanations for why and how misconception correction may fail that may be useful in the design of educational interventions.